The Relationship between Peers and Parental Control on Problematic Smartphone Use - Fadlilah, Tuti' Nurul; Eddy Wibowo, Mungin; Purwanto, Edy (Jurnal Bimbingan Konseling, 2022)
Smartphone is a communication tool designed to facilitate human connectivity via cellular networks. However, various impacts are found in smartphone use, such as compulsive behavior, covering decreased productivity and poor academic performance in students. The research in this papaer examined the relationship between peers and parental control on problematic smartphone use using a correlational design and involving a sample of 317 Madrasah Tsanawiyah (MTs) or Islamic junior high school students. In collecting the data, some instruments were used, namely the Smartphone Addiction Scale (SAS), Peer Relation Scale (PRS), and Parental Bonding Instrument (PBI) which previously have been tested for validity and reliability. Following the collection, the data were analyzed using a hierarchical regression analysis. Findings indicated that peers and parental control had a partial relationship with problematic smartphone use. This finding has confirmed that peers and parental control relationship jointly gives greater contributions on problematic smartphone use rather than peers and problematic smartphone use only. Further results and limitations are discussed in the discussion section. Smartphone usage can also have both positive and negative impacts on children and teenagers. Parental influence is essential in shaping healthy and balanced patterns of smartphone use. This study used an ex-post facto correlation. The subjek this study is junior high school students in the Semarang regency. The sampling technique employed in this was Cluster Random Sampling, with a total sample size of 317 participants. The research utilized the Smartphone Addiction Scale (SAS), Perr Relation Scale (PRS), and Parental Bonding Instrument (PBI) as measurement scales. The results of this study indicated a correlation between peer influence and parental control over problematic smartphone use, with an R Square of 0.035 and p < 0.05, showing a significant relationship between peer influence and problematic smartphone use. Moreover, there was a strong correlation between peer influence and parental control over problematic smartphone use, with an R Square of 0.920 and p < 0.05, indicating that both factors significantly affected problematic smartphone use. The RSquare Change value of 0.885 further confirmed the influence of peer influence and parental control on problematic smartphone use. The conclusion, this research demonstrates a significant relationship between peer influence and problematic smartphone use, as well as a connection between parental control and problematic smartphone use.So that the role of parents in controlling and guiding the use of children's smartphones and adolescents is very important to avoid addiction or excessive use. In addition, an understanding of peer influence also needs to be considered in an effort to reduce problematic smartphone use.